6y-14=-2(y-5)

Simple and best practice solution for 6y-14=-2(y-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y-14=-2(y-5) equation:



6y-14=-2(y-5)
We move all terms to the left:
6y-14-(-2(y-5))=0
We calculate terms in parentheses: -(-2(y-5)), so:
-2(y-5)
We multiply parentheses
-2y+10
Back to the equation:
-(-2y+10)
We get rid of parentheses
6y+2y-10-14=0
We add all the numbers together, and all the variables
8y-24=0
We move all terms containing y to the left, all other terms to the right
8y=24
y=24/8
y=3

See similar equations:

| 7w-4w=36-27 | | -52-x=-7x+50 | | -8(x-4)=-6x+28 | | 5y+7=78 | | 12–2(x+4)=2 | | 3x+2x-6=x+18 | | -8w+6(w-4)=-32 | | 8(h-9)=-16 | | 9m+8=4-6m | | -2x+7-3x=-3 | | 7(x+6)+2=-4(x-2)-8 | | -+12n=12n+9 | | 40=2(8+4x) | | 9+12n=12+9 | | 24x+42=22x | | 2(-x-4)=16 | | 20÷x-7=3 | | 45=2x+3-5x+12 | | 4(3x-1)-5=75x= | | 1/4y=1/18 | | -5(4t-3)+4t=7t-2 | | 2(x-10)+1=60x= | | 8+4x=23-x | | 5(−2n+4)=2(n+3) | | 2/3x+1/2=7 | | 0=-5t^2+40t | | 5(−2n+4)+2(n+3)=8.−7(n+3)−8(3+8n)= | | 16=1-3y | | 2y-61=135 | | 5x+9-8x-30=180 | | (2x-1)/3+x/4=5 | | 32=8+c |

Equations solver categories